Phosphate enrichment increases the resilience of the pulsating soft coral Xenia umbellata to warming - Klinke, Annabell; Mezger, Selma D.; Thobor, Bianca; Tilstra, Arjen; El-Khaled, Yusuf C.; Wild, Christian (Frontiers in Marine Science, 2022)
Hard corals are in decline as a result of the simultaneous occurrence of global (e.g., ocean warming) and local (e.g., inorganic eutrophication) factors, facilitating phase shifts towards soft coral dominated reefs. Yet, related knowledge about soft coral responses to anthropogenic factors remains scarce. We thus investigated the ecophysiological response of the pulsating soft coral Xenia umbellata to individual and combined effects of phosphate enrichment (1, 2, and 8 μM) and ocean warming (26 to 32 °C) over 35 days. Throughout the experiment, we assessed pulsation, mortality, Symbiodiniaceae density, and cellular chlorophyll a content. Simulated ocean warming up to 30 °C led to a significant increase in polyp pulsation and by the end of the experiment to a significant increase in Symbiodiniaceae density, whereas cellular chlorophyll a content significantly decreased with warming, regardless of the phosphate treatment. The combination of phosphate enrichment and simulated ocean warming increased pulsation significantly by 41 – 44 %. Warming alone caused significantly lower pulsation by 11 – 12 % in soft corals at 30 °C compared to soft corals exposed to phosphate enrichment and warming. In contrast to warming alone, phosphate enrichment alone did not affect any of the investigated response parameters. Overall, X. umbellata displayed a high resistance towards ocean warming with no mortality in all treatments. Phosphate enrichment enabled soft corals to significantly increase their pulsation under increasing temperatures which may enhance their resistance towards ocean warming. This, in turn, could further facilitate their dominance over hard corals on future reefs.